Observation of multi-directional energy transfer in a hybrid plasmonic-excitonic nanostructure - Pincelli, Tommaso; Vasileiadis, Thomas; Dong, Shuo; Beaulieu, Samuel; Dendzik, Maciej; Zahn, Daniela; Lee, Sang-Eun; Seiler, Helene; Qi, Yinpeng; Xian, R.Patrick; Maklar, Julian; Coy, Emerson; et al. (Wiley, 2022)
Hybrid plasmonic devices involve a nanostructured metal supporting localized surface plasmons to amplify light–matter interaction, and a non-plasmonic material to functionalize charge excitations. Application-relevant epitaxial heterostructures, however, give rise to ballistic ultrafast dynamics that challenge the conventional semiclassical understanding of unidirectional nanometal-to-substrate energy transfer. Epitaxial Au nanoislands are studied on WSe2 with time- and angle-resolved photoemission spectroscopy and femtosecond electron diffraction: this combination of techniques resolves material, energy, and momentum of charge-carriers and phonons excited in the heterostructure. A strong non-linear plasmon–exciton interaction that transfers the energy of sub-bandgap photons very efficiently to the semiconductor is observed, leaving the metal cold until non-radiative exciton recombination heats the nanoparticles on hundreds of femtoseconds timescales. The results resolve a multi-directional energy exchange on timescales shorter than the electronic thermalization of the nanometal. Electron–phonon coupling and diffusive charge-transfer determine the subsequent energy flow. This complex dynamics opens perspectives for optoelectronic and photocatalytic applications, while providing a constraining experimental testbed for state-of-the-art modelling.
A combined study of electronic and lattice dynamics to observe multi-directional energy transfer in a hybrid plasmonic–excitonic nanostructure.
Keywords: plasmons; excitons; ultrafast energy transfer; transition metal dichalcogenides